Kwentong Jollibee a case study of Jollibee video advertisements' transition from traditional to new platforms - Tejada, Mia Trixia Ella Olarte
This study aims to explain how online media platforms compare to traditional media platforms in promoting Jollibee. This study asks how Jollibee has utilized the online media platform for its video advertisements. Specifically, this study looks at how Jollibee has begun to direct its resources into generating online video advertisements, and ascertains viewership of these materials.